2014
DOI: 10.1007/s00262-014-1613-0
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled phase III trial of adjuvant chemo-immunotherapy with activated killer T cells and dendritic cells in patients with resected primary lung cancer

Abstract: PurposeWe conducted a phase III randomized controlled trial (RCT) to investigate the efficacy of postsurgical adjuvant immunotherapy combined with chemotherapy. The immunotherapy targets were residual micrometastases and clones resistant to chemotherapy.Patients and methodsBetween April 2007 and July 2012, 103 postsurgical non-small cell lung cancer patients were randomly assigned to receive either chemo-immunotherapy (group A) or chemotherapy (group B). The immunotherapy consisted of the adoptive transfer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 32 publications
2
65
0
1
Order By: Relevance
“…Thus far, no clinical trials have been reported that exclusively tested the combination of chemotherapy and DC vaccination, but numerous trials are ongoing in which the combination is being tested with or without additional therapies. Chemotherapy and DC vaccination were tested with the addition of a COX-2 inhibitor in melanoma in a phase III trial showing encouraging data, and with the addition of autologous T cells in lung cancer in two randomized trials showing longer overall survival compared with outcomes from chemotherapy alone (79)(80)(81).…”
Section: Combination With Chemotherapy: An Unexpected Synergistic Effectmentioning
confidence: 99%
“…Thus far, no clinical trials have been reported that exclusively tested the combination of chemotherapy and DC vaccination, but numerous trials are ongoing in which the combination is being tested with or without additional therapies. Chemotherapy and DC vaccination were tested with the addition of a COX-2 inhibitor in melanoma in a phase III trial showing encouraging data, and with the addition of autologous T cells in lung cancer in two randomized trials showing longer overall survival compared with outcomes from chemotherapy alone (79)(80)(81).…”
Section: Combination With Chemotherapy: An Unexpected Synergistic Effectmentioning
confidence: 99%
“…No distant metastases were confirmed by routine examinations for lung cancer using computed t node disse adenocarci chemothera to Novemb dendritic ce The total c number of and lymph mary lung d adjuvant ) from July onths with rgery [6][7][8][9][10] .…”
Section: Case Reportmentioning
confidence: 99%
“…There is much interest in utilizing DC-based vaccines in combination with activated killer T-cells to enhance the host anti-tumor response in lung cancer. Though some early studies have shown promising results in patients with surgically resected non-small cell lung cancer 55 , confirmation in large multi centre studies are needed.…”
Section: Lung Cancer and Mesotheliomamentioning
confidence: 99%